KUALITAS PELAYANAN PENGURUSAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - Simamora, Nopen; Sulistyaningsih, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Birth certificate is a document which describes the status and identity of the child who has legal entities and the State. One of the benefits for society are the birth certificate to get into formal schools. Service of departement population and civil registration Pekanbaru (Disdukcapil) is the agency that has the task and the responsibility of taking care of the birth certificate. The phenomenon that complaints are often perceived by communities where the cost and duration of the completion of the birth certificate does not comply with the rules. The study of influencing quality of service management to figure out the birth certificate at the Office of departement population and civil registration Of Soweto and the factors that affected theConcept of the theory is the theory of Darmawanto. Indicators in this study are: simplicity, clarity, certainty of time, products, and equipment and infrastructure. Type of this research is a descriptive qualitative research. The results showed that the quality of service management of the birth certificate in departement population and civil registration Office Pekanbaru city is less good. This is apparent from deficiencies that occur in The population and civil registration Of Soweto.Keywords: birth certificate, departemen population and civil registration, service quality